Microbial diversity and function in bamboo ecosystems - Wang, Yexuan; Ren, Huimin; Zhong, Yue; Song, Ruisheng; Jiang, Siyuan; Lai, Mengjing; Shen, Yuqi; Liu, Shenkui; Shi, Wenhui; Qi, Guoning (Frontiers in Microbiology, 2025)
Bamboo is widely distributed or cultivated globally, offering significant economic and ecological values. Soil microorganisms are crucial for plant environmental adaptation, playing essential roles in regulating plant growth and development, nutrient absorption, and resistance to environmental stresses. In recent years, substantial progress has been made in the study of bamboo soil microorganisms. This review highlights the scientific challenges in understanding the interactions between bamboo and soil microorganisms, summarizes the research progress, and discusses future research directions. The microbial community composition and diversity in various bamboo soils have been successfully characterized, with some bamboo-associated microorganisms identified and shown to promote plant growth, demonstrating considerable application potential. It has been established that the composition of soil microorganisms in bamboo is influenced by factors such as bamboo species, spatial and temporal distribution, tissue specificity, management practices, and symbiosis with other plants. Future research will likely focus on the functional genomics of bamboo, the screening and identification of bamboo-specific soil microbial communities, the dynamic responses of these microbes to environmental changes, and the molecular mechanisms regulating bamboo growth and environmental adaptation.